KEBIJAKAN PUBLIK UNTUK EKOWISATA DI KALIMANTAN TENGAH Kebijakan Penataan Kawasan Ekowisata Sungai Kahayan di Kota Palangka Raya - Bhayu Rhama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2012)
AbstrakEcotourism is an activity that relies on the daily lives of people and their natural combinations in sustainable conditions. Ecotourism is also an economic foundation of the region that is not own by all regions. The government, surrounding community and the tourists who visit the place is also responsible for maintaining the location’s sustainability andharmony. Central Kalimantan province that has a lot of potential to develop eco-tourism should start immediately so the region’s natures and daily lives is not damaged by mismanagement. Local governments are obliged to issue a Public Policy for ecotourismto improve societies’ welfare that can be started to choose Kahajan River in Palangkaraya as an icon of ecotourism in Central Kalimantan.